An image encryption algorithm based on a 3D chaotic Hopfield neural network and random row–column permutation - Yao, Wei; Gao, Kai; Zhang, Zhihao; Cui, Li; Zhang, Jin (Frontiers in Physics, 2023)
This paper proposed a novel color image encryption algorithm based on a 3D chaotic Hopfield neural network and random row-column permutation. Firstly, a 3D chaotic Hopfield neural network is proposed to produce the random sequence for generating the diffusion keys and permutation keys. Then, the rows and columns of the original image are randomly arranged according to the permutation key in the permutation process. Three subgraphs are formed by separating the R, G, and B components of the color image in the diffusion process. Each subgraph is split along the columns to form three parts, the left and middle parts are exchanged. Three diffusion keys are used to encrypt each of the three parts. Finally, the individually encrypted subgraphs are stitched together to obtain the final encrypted image. Simulation results in Matlab and FPGA and security analysis demonstrate that the encryption scheme has a good performance.